2002
DOI: 10.1183/09031936.02.00241502
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and clinical characteristics of rapid-onset fatal and near-fatal asthma

Abstract: The onset of fatal and near-fatal asthma attacks can be rapid. The objective of this study was to determine the frequency and clinical characteristics of rapid-onset asthma (ROA) in patients suffering fatal and near-fatal crises.Two-hundred and twenty patients with fatal or near-fatal attacks were enrolled in a multicentre, prospective study. ROA was defined as a crisis developing in ¡2 h. Data on patient and clinical characteristics were collected, and spirometric and allergy studies were performed when the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 31 publications
0
54
0
5
Order By: Relevance
“…Studies of rapid-onset and slow-onset attacks of near-fatal asthma have suggested that rapid-onset attacks may have different trigger factors and lower rates of infection than slow-onset attacks cases [30,31].…”
Section: Time To Death In Asthmamentioning
confidence: 99%
“…Studies of rapid-onset and slow-onset attacks of near-fatal asthma have suggested that rapid-onset attacks may have different trigger factors and lower rates of infection than slow-onset attacks cases [30,31].…”
Section: Time To Death In Asthmamentioning
confidence: 99%
“…A detailed description of the method used has been published previously [14]. Briefly, a descriptive prospective multicentric study was carried out in 33 hospitals in Spain.…”
Section: Methodsmentioning
confidence: 99%
“…Hızlı gelişen ataklar birkaç saatte en üst seviyeye varır. Bunlarda CD8 lenfosit ve nötrofil hakimiyeti söz konusudur (23). Esas sorun inflamasyon kadar düz kas kasılma-sının varlığıdır.…”
Section: Astımunclassified
“…Yavaş gelişenler birkaç gün içinde, ortalama 3-7 günde en üst seviyeye gelip, yine bu sürelerde düzelir. Bunlarda CD4 lenfosit ve eozinofil hakimiyeti vardır (23).…”
Section: Astımunclassified